Evaluation of gastric tube blood flow by multispectral camera and fluorescence angiography - Yasuhiro Haruta; Yuichiro Nakashima; Tetsuo Ikeda; Eiji Oki; Tomoharu Yoshizumi (Surgery Open Science, 2024)
Background: Evidence regarding the application of the multispectral camera for blood flow measurement is insufficient, and its performance has not been compared with the conventional indocyanine green (ICG) method. Therefore, we retrospectively compared the effectiveness of a new multispectral camera for non-invasive, real-time, quantitative imaging of tissue oxygen (O2) saturation and hemoglobin (Hb) levels and commercially available ICG fluorescence imaging in hemodynamic assessment of gastric tubes in esophagectomy. Methods: Thirty patients who underwent thoracoscopic esophagectomy and gastric tube reconstruction for esophageal cancer were included in this study. The multispectral camera was used to measure tissue O2 saturation and Hb levels. The ICG fluorescence imaging, with the analysis software tool Lumi view, was employed to record ICG luminance changes, with values measured at the anastomotic site. Furthermore, the usefulness of each assessment device was examined using the arterial and venous blood flow indices as cutoff lines for cases with anastomotic failure. Results: In the evaluation of arterial perfusion, anastomotic leak occurred in three of the five (60 %) patients with arterial insufficiency as assessed by the ICG imaging, while anastomotic leakage occurred in all three patients (100 %) who were assessed as having arterial insufficiency by the multispectral camera. In the evaluation of venous perfusion, anastomotic leakage occurred in three of the nine (33.3 %) patients diagnosed with venous stasis by the IC imaging and in three of the five (60 %) patients assessed by the multispectral camera. Conclusion: The multispectral camera assessed gastric tube blood flow more accurately than the ICG fluorescence method.